2017
DOI: 10.1111/coa.12843
|View full text |Cite
|
Sign up to set email alerts
|

The utility of intra‐operative frozen section for the evaluation of microscopic extrathyroidal extension in papillary thyroid carcinoma

Abstract: Intra-operative frozen biopsy can be a useful method for identifying the microscopic ETE. During the surgery, it can also help the surgeon to decide the optimal extent of surgery and the need for central compartment neck dissection in PTC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Of 300 thyroid cancer patients, positive sentinel lymph nodes were identified in 43 cases, and FS failed to predict lymph node involvement in 10 cases (sensitivity and specificity of 89.6% and 100%, respectively). Similar finding was also reported by Hong et al 22 and the present study findings as well suggest the high reliability of FS biopsy in lymph node status assessment.…”
Section: Discussionsupporting
confidence: 93%
“…Of 300 thyroid cancer patients, positive sentinel lymph nodes were identified in 43 cases, and FS failed to predict lymph node involvement in 10 cases (sensitivity and specificity of 89.6% and 100%, respectively). Similar finding was also reported by Hong et al 22 and the present study findings as well suggest the high reliability of FS biopsy in lymph node status assessment.…”
Section: Discussionsupporting
confidence: 93%
“…18,19 However, a recent study by Hong et al, demonstrated that an intraoperative frozen biopsy can be useful in determining whether the PTC has a microscopic extra-thyroid extension (high-risk feature) and therefore affects the extent of the surgery. 20 Another study by Estebe et al reported that an intraoperative FS has higher sensitivity and specificity compared to a preoperative fine needle aspiration cytopathology (FNAC). 21 These authors also concluded that intraoperative FS reduced the number of unjustified total thyroidectomies and the need for two-staged procedures (conservative hemithyroidectomy followed by completion thyroidectomy).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, microscopic extrathyroidal extension can only be detected by pathological microscopic examination. [ 34 ] The number of studies on the effectiveness of FS in extrathyroidal extension is limited in the literature. First of all, Park et al [ 35 ] studied the effectiveness of FS in evaluating extrathyroidal extension in papillary thyroid cancer.…”
Section: B Frozen Section Examination In Assessment Of Extrathyroidal...mentioning
confidence: 99%
“…In another study, where microscopic extrathyroidal extension was 27.5% in papillary thyroid cancer, it was reported that intraoperative FS could detect microscopic extrathyroidal extension with 100% sensitivity and specificity in all cases. [ 34 ] Both studies reported that intraoperative FS can be used to detect extrathyroidal extension in papillary thyroid cancer, and FS can assist the surgeon in determining the extent of thyroid surgery and central dissection. FS examination can be used to evaluate extrathyroidal spread, especially if the treatment plan will change in patients with papillary thyroid cancer.…”
Section: B Frozen Section Examination In Assessment Of Extrathyroidal...mentioning
confidence: 99%